The cardiovascular response to international Olympic class windsurfing competition - Anastasiou, A.; Jones, T.; Mullan, P.; Ross, E.; Howatson, G. (International Journal of Sports Science & Coaching, 2025)
This study aimed to quantify the cardiovascular demands of the two predominant techniques within international Olympic windsurf competition. Three male (23 ± 3 y, 73.0 ± 1.4 kg, 181.3 ± 5.3 cm) and 3 female (26 ± 9, 60.1 ± 1.7 kg, 169.8 ± 3.2 cm) elite windsurfers competing at two international regattas were recruited. Windsurfers wore a heart rate (HR) monitor, whilst global positioning system data was gathered from an online website (SAP® Analytics). Races were categorised as either pumping or planing. Both average (88 ± 3 vs. 83 ± 4%) and peak (95 ± 2 vs. 91 ± 4%) HR was higher (P < 0.001) in pumping. Furthermore, the time spent in zone 5 was greater (44 ± 27 vs. 9 ± 11%, P < 0.001) in pumping. Furthermore, planing covered more distance (+ 4875 m, P < 0.001) at greater speeds (+ 9.3 knots, P < 0.001). Whilst pumping resulted in longer race times (+ 07:56 mm:ss, P < 0.001). These findings support the optimisation of training prescription and development of performance testing for Olympic windsurfers. Furthermore, the study design has demonstrated a practical approach to understanding the cardiovascular demands across different Olympic sailing classes.